Grouping Library Book Collection Based On Old Book Borrowers With Clustering Method (Case study: STMIK Kaputama) - Sumartika Br Hutasoit; Budi Serasi Ginting; Fuzi Yustika Manik (CV. AFDIFAL MAJU BERKAH, 2024)
Libraries are institutions that collect printed and recorded knowledge. Books can be borrowed at the library for a length of time according to library regulations. Based on observations that some types of books in the library of STMIK Kaputama have a very high ratio of the number of borrowers, while the availability of books is limited. The addition of new book collections cannot be done because the storage capacity of the collection is limited. Based on these conditions, the grouping of book collections based on the length of book borrowing is carried out to optimize the service time for borrowing books. This application was created to assist librarians in determining the optimal length of book borrowing. So in this case, we will design and build a system that will be used in grouping library book collections based on the length of borrowing and the variables determined using the clustering method. The purpose of this research is to design and build a system for grouping library book collections in order to produce information quickly about the availability of books in the library.